CROSS-CULTURAL COMPARISONS OF ONLINE AND FACE-TO-FACE EDUCATION: METHODOLOGICAL CHALLENGES - Khudoyqulova Sevara Saidakbarovna (International Journal of Literature and Language Studies, 2026)
The rapid development of digital technologies and the global impact of the COVID-19 pandemic have significantly transformed educational systems worldwide. This transformation intensified the comparison between online and face-to-face education across different cultural contexts. The present study investigates methodological challenges in cross-cultural comparisons of online and traditional classroom learning. The research applies the IMRAD structure and relies on statistical reports, international educational surveys, and comparative analysis methods. Findings indicate that socio-cultural values, technological infrastructure, digital literacy, language barriers, and pedagogical traditions considerably influence learning outcomes and students’ engagement in different educational environments. The study emphasizes that methodological inconsistencies often limit the reliability of international comparisons. The article concludes that future educational research should integrate culturally adaptive methodologies and mixed-method approaches to ensure accurate evaluation of educational effectiveness.